Improving Students’ Toefl Listening Skill through Task-Based Learning Approach - Juliana Juliana (Budapest International Research and Critics University, 2021)
Toefl is urgently needed as an administrative requirement to work and participate in the scholarship competition. Students are required to master skills of this test. However, based on the results of pre-observations conducted in Information System class of Potensi Utama University, it is known that the average Toefl scores of students in Reading (37.8%), structure (32.7%), and Listening (29.5%). This phenomenon occurs because Toefl learning emphasizes a lot of activities on reading and structure skills so students do not get listening tasks with good quality and quantity. Therefore, the effective learning approach is needed to make Toefl learning process more effective in improving the listening skill of students. The result showed that there was an Improving of students’ listening skill from the test results of before observation with the highest conversion score of students’ Toefl listening is 43. Meanwhile, after being given action and application of task-based learning approach there was a change that the highest score of students’ Toefl listening in cycle I is 54 and the highest score of students’ Toefl listening in cycle II is 62. Therefore, it can be concluded that using the task-based learning approach has significantly improved students' Toefl listening skill.